El sistema del conocimiento comprensivo procesual: fundación teórica, verificación empírica y diseño pedagógico con aplicación a la pedagogía preventiva: producto pedagógico - Berzosa Peralta, José Luis (2013)
The main contribution of our research leads to the think again the salesian pedagogy. Specifically we want to give a new epistemological argument for the strengthening of preventive system of Don Bosco, in perspective of answer the challenges that the youth ask to education system today, inside the educational reality of our country. Be preventive means more than to avoid bad behaviors happen. And reason, religion and love are no more separated fields. From our research, based in philosophical and cognitive theories, be preventive means to support the way in which the students becomes more dynamic while they learn. They make the movements, they have the experiences while they resolve problems, plan their future and reflect about their own vocation